2012
DOI: 10.1159/000336598
|View full text |Cite
|
Sign up to set email alerts
|

Clock Test Deficits Related to the Global Cognitive State in Alzheimer’s and Parkinson’s Disease

Abstract: Background/Aims: Clock drawing (CD) seems to be impaired quite early in the process of cognitive decline in Parkinson’s disease (PD). Methods: We assessed performance on the CD test (CDT), clock setting test (CST) and clock reading test (CRT) in 32 elderly healthy controls, 41 patients with PD, 23 patients with amnestic mild cognitive impairment (aMCI) and 40 patients with Alzheimer’s dementia (AD). Our focus was on comparing the performance of PD and aMCI/AD patients in relation to their global cognitive stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
13
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 85 publications
7
13
1
Order By: Relevance
“…For instance, terms such as response to ethanol, positive regulation of interleukin-6 production, xenobiotic metabolic process, and neurotransmitter biosynthetic process were significantly enriched in PD-related genes, indicating the importance of these activities in the pathologic processes of PD. Of significance, we found that the GO biological process terms of visual learning, sleep, and memory were also in the enriched list, in line with previous findings of various [59][60][61], involved in PD. Pathway analysis revealed that immunologic systemrelated pathways were enriched in PDgset, which further consolidates ties between the pathology of PD and immune-specific activities.…”
Section: Discussionsupporting
confidence: 90%
“…For instance, terms such as response to ethanol, positive regulation of interleukin-6 production, xenobiotic metabolic process, and neurotransmitter biosynthetic process were significantly enriched in PD-related genes, indicating the importance of these activities in the pathologic processes of PD. Of significance, we found that the GO biological process terms of visual learning, sleep, and memory were also in the enriched list, in line with previous findings of various [59][60][61], involved in PD. Pathway analysis revealed that immunologic systemrelated pathways were enriched in PDgset, which further consolidates ties between the pathology of PD and immune-specific activities.…”
Section: Discussionsupporting
confidence: 90%
“…The executive functions impairment in AD patients is usually less intense than the one found in patients with more pronounced frontal lobe damage, such as frontotemporal dementia, focal brain lesions and subcortical dementias (Liscic, Storandt, Cairns & Morris, 2007;Boban, Malojcic, Mimica, Vukovic & Zrilic, 2012;Yoon et al, 2013;Saur et al, 2012). Since the FAB is a screening test, its accuracy for detecting executive impairment in AD patients may be limited, and that evaluation should be complemented with neuropsychological tests designed for the assessment of more specific components of executive functioning, such as inhibitory control (Balota et al, 2010;de Paula et al, 2012b), planning (de Paula et al, 2012a, cognitive shifting (Hamdan, & Hamdan, 2009), decision making (Malloy-Diniz et al, 2008), working memory (Wood, Carvalho, Neves & Haase, 2001) and ecological executive performance (Pereira, Oliveira, Diniz, Forlenza & Yassuda, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the relatively low sensitivity of this test in assessing visuospatial performance. In clock drawing tests, patients with Parkinson’s disease (and no dementia) make more errors than healthy controls (Dal et al , 1989; Stella et al , 2007; Saur et al , 2012) and errors in drawing houses are also reported in Parkinson’s disease (Kulkarni et al , 2013). However, all these tests lack specificity for visuospatial function as they involve several cognitive domains in addition to visuospatial processing, including praxis, memory and executive function.…”
Section: Evidence For Changes In Visual Processingmentioning
confidence: 99%